SEMI PURIFIKASI DAN UJI REAKSI TRANSGLUKOSILASI P-GLUKOSIDASE DARI Aspergillus pulverulentus - Joko Sulistyo; Yati Sudaryati Soeka; Purnama Dewi (Research Center for Biology-Indonesian Institute of Sciences, 1998)
An extracellular p-glucosidase[EC 3.2.1.21]derived from Asvereillus vulverulentus were separated and partially purified by successive chromatographies and its some characterization and transglucosylation capacity were studied.The purification protocol included precipitation with ammonium sulphate,gel filtration,ion exchange chromatography and native polyacrylamide gel electrophoresis.The enzyme readily hydrolysed cellobiose to form transglucosylation products in the present of primary alcohol acceptors.This P-glucosidase was stable at temperatures up to 70 °C and from pH 2.5 to 8.5, while its highest activity was in the pH 4.5 at 65°C.